PELAKSANAAN KEBIJAKAN EKONOMI PADA MASA KEKHALIFAHAN UMAR BIN KHATTAB (634 – 644 M) - Dody Hermanto; Kamaruddin Oemar; Asril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Problem of writing this essay is economic policy execution at a period leadership of Umar during ten years a period of its governance. Intention of this research that is knowing any kind of policy during a period of governance, how policy execution and what affect from the policy. Expected from writing of this essay can give benefit to writer and also to reader to add knowledge concerning Islam history specially history leadership of Umar bin Khattab. Method Research of this essay is used history method by using Heuristik stages;steps, verification, Historiografi and interpretation with data collecting use bibliography study technique. Result of from writing of this erudite masterpiece include;cover any kind of economic policy of Umar leader and how its execution for example including Policy between two fires Ramadah year, Monetary policy by printing first Islam dram money, Baitul mal independency and bookkeeping of state financial administration, management of natural resources and hisbah observation of market. From result of research can be concluded, that economic policy at a period of leadership of Umar bin Khattab caused of Umar wisdom and intellegence as leader with its ijtihad and conducted deliberation with friend. Expected with writing of this erudite masterpiece can give guidance and reference to governance execution in arranging economics of state.Keywords: Economic Policy, Governance of Islam, Umar bin Khattab